Descriptive catalogue of Quaid-i-Azam papers (Pakistan. Education Division. Quaid-i-Azam Papers Cell. Publication, 1971)
Documents of and about Quaid-i-Azam Mahomed Ali Jinnah 1876-1948, founder of Pakistan.